Construction of a novel oligonucleotide array‐based transcription factor interaction assay platform and its uses for profiling STAT1 cofactors in mouse fibroblast cells. Issue 16 (22nd July 2013) - Zeng, Lingqin; Sun, Yimin; Xie, Lan; Wei, Li; Ren, Yonghong; Zhao, Jianqing; Qin, Wenyan; Mitchelson, Keith; Cheng, Jing
<x xml:space="preserve">Abstract</x> Here, we describe a novel oligonucleotide array‐based transcription factor (TF) interaction assay platform that can directly identify cointeracting TF complexes following binding to their regulatory DNA elements. This platform that combines immuno‐coprecipitation technology with our previously reported oligonucleotide array‐based TF assay (OATFA), is named targeted immuno‐coprecipitation OATFA (TIC‐OATFA). We illustrate use of the system to identify interaction partners of STAT1 (signal transducer and activator of transcription proteins 1) in mouse fibroblasts. Several previously known partners of STAT1, as well as new partners, were identified by TIC‐OATFA, including the upstream stimulatory factors 1 and 2 (USF1, USF2), nuclear factor of activated T cells, TATA box‐binding protein, nuclear factor erythroid‐derived 2, nuclear factor‐kappa B, and nuclear factor 1. Both USF1 and nuclear factor‐kappa B are well known to interact with STAT1, but the other five TFs are previously unreported STAT1 interaction partners. We examined interactions between one new TF, USF2, and STAT1 in detail. USF2 belongs to the group of bHLH‐zip transcription factors, which in a number of diseases including cancers, has enhanced activity. In summary, a novel oligonucleotide array‐based assay platform was developed and used to study interactions between STAT1 and functional TF binding partners, revealing that USF2 and potentially four other new TFs are partners of STAT1 in an IFN‐γ stimulated mouse fibroblast cell line.